NEW DATA ON SOME MOTH SPECIES (LEPIDOPTERA) FROM MT. JADOVNIK AND MILEŠEVKA RIVER CANYON (WEST SERBIA) - Jakšić, Predrag; King, Andrew (Bulletin of Natural Sciences Research, 2021)
Data on six species of Lepidoptera significant for the fauna of Serbia, as the data on one quite rare species in Serbian fauna are presented.